The protsessno-focused re-structuring of the enterprise of mechanical engineering: from the theory to practice - A. Afanasev (Модернизация, инновация, развитие, 2016)
In the developed uneasy economic conditions, re-structuring - one of the most effective methods who can influence positive change of a machine building complex, its organizational-technical, administrative and legal orientation. Necessity of a theoretical and methodical readiness of investigated problems and their practical importance have caused an urgency and a choice of a theme of article. The purpose / problems. Enterprise re-structuring as a practical embodiment of the purposes of managers, is a difficult, multifactorial problem. Accordingly, the decision of this problem, namely construction of the protsessno-focused re-structuring of the enterprise demands the complex, system approach. Article purpose is – the description of methodology of one of possible approaches to transformation of re-structuring of the enterprise of mechanical engineering from the point of view of practical management.Methodology. In article the methodology is resulted, allowing to solve the questions connected with re-structuring at the enterprises of mechanical engineering owing to consistency .Results. The present article is short describes the practical scientifically-methodical approach in which frameworks was construction of the protsessno-focused re-structuring of the enterprise of mechanical engineering on an example of the largest enterprise of Privolzhsky federal district of Open Society "Кamaz" is offered.Conclusions / the importance. Undoubtedly, offered approach – is not unique. However it has essential advantages before others – the consistency and application in aggregate both the conventional tools of management, and the original workings out which have proved the practical suitability in the conditions of the Russian practice. This approach – not panacea from all troubles of the real enterprise. Nevertheless, as practice shows, he allows to reach notable successes at carrying out of transformations real, instead of the theoretical enterprises working in the conditions of the Russian economy.